The Modeling of Tsunami Effect to The Agriculture Sector in Padang, West Sumatra Province - Frananda, Hendri; Pradana, Fadli (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
If a tsunami comes there are several impacts i.e the most material loss and fatalities especially in the coastal area of densely populated such as Padang, West Sumatra. The research about the modeling of tsunami damage and effect is needed as the government references in the policy-making about the city layout. In this modeling, the tsunami has the sea level as much as 11 meters in the shoreline. Then we will calculate the decreasing water level which is blocked by the areas used. To know the land effected is used Cost-distance analysis. The indicator of area damage calculated in the agriculture sectors are the rice fields, farms, and fields. The modeling results showed that the rice fields have impact as wide as 2. 090,36 ha or 38% from the total area of rice fields, while the fields have impact as wide as 663,86 ha or 23,10% from the fields total area and the farms have impact as wide as 829,73 ha or 8,15% from the total area.